2012
DOI: 10.1111/j.1349-7006.2012.02206.x
|View full text |Cite
|
Sign up to set email alerts
|

Pericellular pH homeostasis is a primary function of the Warburg effect: Inversion of metabolic systems to control lactate steady state in tumor cells

Abstract: 2.0 Summary The Warburg effect describes a heightened propensity of tumor cells to produce lactic acid in the presence or absence of O2. Currently, a generally held notion is that the Warburg effect is related to energy. Using whole-genome, proteomic MALDI-TOF-MS and metabolite analysis, we investigate the Warburg effect in malignant N2a cells. The findings show that the Warburg effect serves a functional role in regulating acidic pericellular pH (pHe), which is mediated by metabolic inversion or a fluctuating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
45
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 56 publications
(94 reference statements)
3
45
0
1
Order By: Relevance
“…Our data demonstrate that in the tumor models used in this study, LDH-A expression and pimonidazole binding (primarily dependent on low pO 2 ) (41) have similar but discordant spatial distributions, in good agreement with previous reports that lactic acidosis and hypoxia are not always interdependent (9,38,39). It is likely that tumor regions of poor vascularity and low pO 2 will also possess excess extracellular H + ions due to anaerobic glucose metabolism and local lactic acidosis.…”
Section: Discussionsupporting
confidence: 89%
“…Our data demonstrate that in the tumor models used in this study, LDH-A expression and pimonidazole binding (primarily dependent on low pO 2 ) (41) have similar but discordant spatial distributions, in good agreement with previous reports that lactic acidosis and hypoxia are not always interdependent (9,38,39). It is likely that tumor regions of poor vascularity and low pO 2 will also possess excess extracellular H + ions due to anaerobic glucose metabolism and local lactic acidosis.…”
Section: Discussionsupporting
confidence: 89%
“…The precise role of COX7A1 is not yet clear, however, two recent studies in mice reveal that a COX7A1 knockout gives rise to a cardiomyopathy phenotype with reduced Complex IV activity but increased ATP production [55] while a deletion of the heart-isoform of COX7A1 impairs muscle angiogenesis and OXPHOS [61]. Interestingly, COX7C has been shown to be phosphorylated and may play a signaling role [62] and in a separate study, the expression of COX7C was identified as one of several proteins regulated in the switch between glycolysis and OXPHOS in tumor cells [63]. In either case, it would appear that loss of one or both of these subunits from Complex IV would have a direct impact on the biochemistry of the MRC and could predispose the cells towards a metabolic situation that promotes tumor growth.…”
Section: Resultsmentioning
confidence: 98%
“…In addition to boosting tissue invasiveness, migratory potential [245,268] and altering drug sensitivity [269,270], an acidic culture condition can have profound effects on other aspects of cancer. Changes to metabolic patterns have been observed when cancer cells are cultured in acidic conditions, with a switch from reliance on aerobic glycolysis and production of lactic acid under a physiological pH to a reversion back to oxidative phosphorylation in an acidic environment [271]. Furthermore, culturing cancer cells in an acidic environment have also been demonstrated to increase autophagic flux [272] and reduce cell sensitivity to radiation therapy, potentially through prolonging the G2/M cell cycle arrest and allowing more time for repairing radiation-induced damage [273,274].…”
Section: Acidic Culture Conditionsmentioning
confidence: 99%